The Buddy Ballooning Technique- A simple debulking technique - Vincent Dangoisse (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
The author describes a simple and inexpensive way to deliver high pressures within an atherosclerotic coronary artery and reports two cases. The technique used two non-compliant (NC) balloons placed in parallel and inflated together within the same coronary segment. The cases illustrate two possible indications for the technique: lesion resistant to one adequately sized NC balloon or not fully expanded coronary stents after high-pressure non-compliant ballooning.